Associação entre consumo alimentar e asma na população adulta brasileira: dados da Pesquisa Nacional de Saúde (PNS)2019 - Parreira, Erika Cardoso Abud (2024)
Asthma is a Chronic Non-Communicable Disease (CNCD) characterised by a chronic inflammatory process in the bronchi of the lungs. For a clinical diagnosis of asthma, one or more of the following symptoms must be present: wheezing (the main characteristic), dyspnoea, chest tightness and a dry cough, particularly at night or early in the morning. It is estimated that asthma affects 235 million people worldwide. In recent decades, the increased prevalence of this disease has been associated with environmental, behavioural and dietary changes. In children, some studies have shown a positive association between asthma and the consumption of ultra-processed foods and there is an indication of protection with the consumption of fresh/minimally processed foods. In adults, no significant association was observed between consumption of ultra-processed foods and asthma. Diet is a modifiable factor and can therefore be intervened to reduce the risk of asthma in individuals with a predisposition to the disease. The aim of this study was to assess the association between food consumption and asthma in the Brazilian adult population. This was a cross-sectional study using data from the National Health Survey (PNS, 2019) of 88,531 Brazilian adults. The exposures were two food scores, produced by combining the frequency of consumption of fresh foods and ultra-processed foods (UPP) on the previous day. Thus, a person who reported having consumed 5 UPP had a score of 5. Subsequently, each group was divided into tertiles, the first tertile being the one with the lowest level of food consumption and the third with the highest level of food consumption. The outcome was the self-reported medical diagnosis of asthma. Logistic regression analyses were carried out using Stata 17.0 software, with adjustments for age (years), race/colour (white/black/yellow/brown/indigenous), sex (female and male), smoking (yes and no), schooling (incomplete primary/complete secondary/complete higher education), alcohol consumption (I don't drink/less than once a month/ once a month or more), physical activity (yes and no), per capita income (Brazilian reals) and area of residence (urban or rural). Associations with p<0.05 were considered significant. The prevalence of a medical diagnosis of asthma was 5.5 per cent, and the UPP and in natura/ minimally processed scores ranged from 0.54 to 4.99 and 3.99 to 9.01, respectively. In adults, the UPP score was positively associated with asthma (OR3rd tertile=1.31 95%CI: 1.11-1.53). On the other hand, the in natura food score was not associated with the diagnosis of the disease (OR 3rd tertile = 0.92 95% CI: 0.80-1.07). The study concluded that Brazilian adults who consumed more ultra-processed foods the day before the interview were more likely to be diagnosed with asthma than those who consumed less than one ultra-processed food the day before the interview.